Pengembangan Sistem Monitoring Kesehatan Berdasarkan Detak Jantung dan Suhu Tubuh Berbasis Internet of Things dengan Metode Fuzzy Mamdani - Bashori, Fandi Achmad; Dirgantoro, Guruh Putro; Wahyudi, Sunu (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2024)
The progress of innovation and data is currently very fast, one sign of which is the presence of the Internet of Things (IoT). IoT is an internet service that is integrated by utilizing certain types of sensorsIn the health sector, both the patient treatment process and the development of health science technology itself is experiencing rapid technological advances. The purpose of this research is to build a health monitoring system based on heart rate and body temperature based on the Internet of Things. The method used in this study is Prototyping.Prototyping is a software development method, which is in the form of a physical working model of the system and functions as an initial version of the system. The prototype of this tool is used to monitor the health of the human body through heart rate and body temperature in humans, namely by using a Pulse sensor and DS18B20 temperature sensor in hand then the results of the sensor readings will appear on the LCD and then configured on the Blynk application on the Smartphone . Based on the results of analysis and testing of health monitoring tools based on heart rate and body temperature based on the Internet of Things. Development of a health monitoring system based on heart rate and body temperature based on the Internet of Things has been made with various electronic components, namely NodeMCU ESP8266, Pulse sensor, DS18B20 temperature sensor , and also a 2x16 LCD. Testing the pulse sensor and temperature sensor DS18B20 is able to detect heart rate and body temperature by holding the two sensors